MODEL EVALUASIPENDIDIKAN MELALUI KEGIATAN BAHTSUL MASAIL DI PONDOK PESANTREN ASSALAFIYYAH1 SUKABUMI - Palah, Palah (Prodi PAI IAILM Suryalaya, 2018)
This paper focuses on the discussion of learning evaluationmodels conducted by Assalafiyyah 1 Islamic boarding school inSukabumi. The discussion method used is literature study and fieldresearch, data collection is done through interviews, observations, anddocumentation studies. The results of the study show that (1) pesantrenhas a commitment to form students who have intellectual, emotionaland spiritual intelligence which is done through the evaluation ofbahtsul masail. (2) the implementation of bahtsul masail activities inAs-Salafiyyah 1 has generally been effective and efficient and inaccordance with what is expected both by purta santri and femalesantri; and (3) the success of the Bahtsul Masail learning evaluationmodel at Assalafiyyah 1 Islamic boarding school in Sukabumi providessubstantial benefits for students in studying the yellow book.